THE RELATIONSHIP OF ENVIRONMENTAL FACTORS AND A HISTORY OF DIARRHEA TO THE INCIDENCE OF STUNTING IN BADUTA AGED 6-23 MONTHS - Siti Novianti; Agus Nurjaman (International Journal of Health Science & Medical Research, 2022)
Stunting is a short or very short state that is based on height according to age. Factors that influence the occurrence of stunting consist of direct factors, indirect factors, and the root of the problem. Environmental factors are indirect factors for the incidence of stunting, where a history of infectious diseases is a link between environmental factors and stunting events. The purpose of this study is to determine the relationship between environmental factors and a history of diarrheal disease to the incidence of stunting in baduta aged 6-23 months in 2021 in the work area of the Ciawi Health Center, Tasikmalaya Regency. The research method used is a quantitative method with a case-control research design. The sample in this study was 102 Badura mothers consisting of 51 stunted baduta mothers and 51 non-stunted baduta mothers. The statistical test used is Chi-Square with (α) = 0.05. The results of the study found that there was a relationship between a history of diarrhea (p-value = 0.031, OR = 5.976), access to sanitation (p-value = 0.034, OR = 4.02) and access to drinking water (p-value = 0.006, OR = 4.453) with stunting events. Meanwhile, there is no relationship between access to sanitation (p-value = .1,000) and access to drinking water (p-value = 0.482) with a history of diarrhea. The conclusion of this study is that the variables associated with stunting events are a history of diarrhea, access to sanitation, and access to drinking water. Meanwhile, access to sanitation and access to drinking water is not related to a history of diarrhea. It is hoped that households can improve sewage channels so that access to sanitation is safe and drinking water sources are safe for consumption.Keywords: Stunting; Baduta; History of Diarrhea; Sanitation; Drinking Water